Food avoidance behaviour among children aged 2 – 6 years in North Jakarta and its correlation with weight and energy intake - Luh Ade Ari Wiradnyani; Alfi Rahma Putri; Dian Novita Chandra (World Nutrition Journal, 2021)
Background: Children generally facing food avoidance or food refusal behaviour and it may affect their food consumption. But there is limited information on food avoidance behaviour among Indonesian children. Therefore, this study aimed to assess whether energy intake and body weight are influenced by food avoidance behaviour in children aged 2-6 years in North Jakarta.Methods: Participants (N=168) were recruited between February – March 2020. Data collection was obtained via interviews with the mother or caregiver of the children. Food avoidance behaviour consisting of satiety responsiveness, slowness in eating, emotional under-eating, and food fussiness was measured with the Child Eating Behaviour Questionnaire. The child’s weight and dietary intake were assessed using a digital weighing scale and 2 x 24 hours food recall. Spearman test was performed to analyse the correlation between these variables. Multivariate analysis was done using linear regression to determine predictors of a child’s body weight and energy intake.Results: Energy intake among children was below the recommendation, and it was significantly correlated with the child’s body weight. Satiety responsiveness was negatively correlated with the child’s body weight (r = -0.166; p-value < 0.05) and energy intake (r = -0.210; p-value < 0.05). After running a linear regression test, we found that satiety responsiveness along with family income and child’s age was a significant predictor of energy intake among children.Conclusions: Children who are more responsive to satiety had lower body weight and energy intake. Understanding the child’s food avoidance behaviour is useful for designing intervention programs related to optimizing intake in children and malnutrition.